Structural insight into the interaction of O‐acetylserine sulfhydrylase with competitive, peptidic inhibitors by saturation transfer difference‐NMR. Issue 7 (22nd March 2016) - Benoni, Roberto; Pertinhez, Thelma A.; Spyrakis, Francesca; Davalli, Silvia; Pellegrino, Sara; Paredi, Gianluca; Pezzotti, Angelica; Bettati, Stefano; Campanini, Barbara; Mozzarelli, Andrea
Abstract : O ‐acetylserine sulfhydrylase (OASS), the enzyme catalysing the last step of cysteine biosynthesis in bacteria, is involved in antibiotic resistance and biofilm formation. Since mammals lack OASS, it is a potential target for antimicrobials. However, a limited number of inhibitors has been developed and crystallized in complex with OASS. STD‐NMR was applied to study the interaction of the inhibitory pentapeptide MNYDI with the CysK and CysM OASS isozymes from Salmonella Typhimurium . Results are in excellent agreement with docking and SAR studies and confirm the important role played by the C‐terminal Ile5 and the arylic moiety at P3 in dictating affinity. Abstract : Cysteine can be synthesized in bacteria by either one of the two isozymes CysK and CysM. STD‐NMR allows to study protein‐ligand binding specificity in solution. Peptidic inhibitors of the two isozymes with MNX1 X2 I sequence have been developed. An arylic substituent at position X1 improves affinity for CysK. The N‐terminal amino acids dictate the specificity for CysM.